PENGARUH MODEL PjBL ( PROJECT BASED LEARNING ) TERHADAP KEMAMPUAN PENALARAN ADAPTIF SISWA DALAM PEMBELAJARAN IPAS KELAS IV DI SDN 26 SINGKAWANG - Relita; Evinna Cinda Hendriana; Wasis Suprapto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aimed to: 1) determine the influence of the Project-Based Learning (PjBL) model on students' adaptive reasoning ability, 2) quantify the improvement in this ability within IPAS learning. This quantitative study employed a pre-experimental one-group pretest-posttest design. The research subjects were 30 fourth-grade students at SDN 26 Singkawang. Data was collected through an adaptive reasoning ability test. Before hypothesis testing, a Shapiro-Wilk normality test was conducted, revealing that both pre-test (Sig. = 0.095) and post-test (Sig. = 0.194) data were normally distributed, thus meeting the requirements for parametric testing. The data analysis techniques used were the paired sample t-test and N-Gain calculation. The results showed that: (1) there was a significant increase in students' adaptive reasoning ability after the implementation of the PjBL model, with the average pre-test score of 55.8 increasing to 74.9 on the post-test. The paired sample t-test yielded a significance value (2-tailed) of 0.000, which is less than 0.05, indicating a significant difference between the pre-test and post-test scores. (2) the N-Gain calculation showed an average value of 73.22%, which falls into the high category. Therefore, it can be concluded that the application of the Project-Based Learning (PjBL) model is effective and has a significant impact on improving the adaptive reasoning ability of fourth-grade students in IPAS learning at SDN 26 Singkawang.